SEMIOTIC STUDY OF TRAFFIC SIGNS IN PADANG - KEVIN WIRA YUDHA (STBA Prayoga Padang, 2018)
The aims of the research was to find the signified and signifier of linguistic signs and signified and signifier of non-linguistic signs of traffic signs in Padang. The writer was interested in the theme because the use of signified and signifier in a sign is important. The object of the study is the signs located on Khatib Sulaiman Street, Padang. The type of the research is qualitative research. In collecting the data, the writer used purposive sampling technique. It means that the data were selected based on characteristic or criteria from the writer. The writer found ten traffic signs that were qualified for the study and divided them into linguistic sign and non-linguistic sign. The writer found that there were eight non-linguistic signs and two linguistic signs. All of the signs contained signified andsignifier on the sign. The signs were simple and understandable for the drivers. Without the signified and signifier, a sign was useless because it became misunderstood and did not have any meaning. The writer gives two suggestions for the next researcher. First, the next researcher can develop more about the sample of the traffic sign. Second, the next researcher can take different theory because the experts for semiotic are quite a lot.